Vin på nya breddgrader - En studie om klimatförändring och resiliens i skånsk vinodling - Andrén,Hanna (2025)
As climate change reshapes agricultural possibilities across Europe, new crops are emerging in previously marginal regions. In Skåne, southern Sweden, commercial wine production has expanded in recent years. This study explores how local winegrowers perceive the role of climate change in this development, what climate-related risks and opportunities they foresee, and what strategies they adopt to enhance resilience and sustainability. Based on semi-structured interviews with nine wine producers, the study uses thematic analysis to examine how climate change is interpreted and integrated into practice. While a warmer climate is acknowledged as enabling, most growers emphasize other drivers—such as improved knowledge, technology, and resilient grape varieties (PIWIs). Climate change is thus seen more as a discursive opportunity than a singular cause. Participants express both concern and cautious hope: while extreme weather, pests, and long-term uncertainty pose threats, longer growing seasons and regional branding are seen as possible benefits. Despite the absence of formal adaptation plans, growers show a readiness to learn and adjust—signaling a form of everyday resilience. The findings underline how climate narratives intersect with local identity, innovation, and land-use decisions. However, they also raise ethical concerns: there is a risk of romanticizing viticulture in the shadow of climate change or overlooking tensions around land use—particularly in a region with highly fertile soils. The study calls for further research on how adaptation intersects with broader sustainability goals, including food security and equity in agricultural transitions.